1998
DOI: 10.1177/112067219800800210
|View full text |Cite
|
Sign up to set email alerts
|

Ocular and Orbital Complications following the Treatment of Retinoblastoma

Abstract: Ocular complications after treating children with retinoblastoma are common and may seriously affect the quality of life of children surviving the primary malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 20 publications
1
23
0
1
Order By: Relevance
“…Radiation retinopathy is caused by an occlusive microangiopathy manifested by microaneuvrysms, retinal hemorrhages, macular edema, and vitreous hemorrhage. In general, radiation retinopathy occurs at doses in excess of 4500 cGy; Anteby et al [17] showed that radiation retinopathy developed in 12% of long-term survivors and was ® rst detected 11± 72 months after treatment.…”
Section: Discussionmentioning
confidence: 98%
“…Radiation retinopathy is caused by an occlusive microangiopathy manifested by microaneuvrysms, retinal hemorrhages, macular edema, and vitreous hemorrhage. In general, radiation retinopathy occurs at doses in excess of 4500 cGy; Anteby et al [17] showed that radiation retinopathy developed in 12% of long-term survivors and was ® rst detected 11± 72 months after treatment.…”
Section: Discussionmentioning
confidence: 98%
“…This dose is much higher than and almost double that used in patients with retinoblastoma; however, it is a standard dose of postoperative radiation in the head and neck for a variety of histologies, including melanoma and squamous carcinoma. Many articles in the literature discuss the role of external beam radiation therapy in retinoblastoma, 814 and the radiation doses described in these articles range from 30 to 55 Gy. Nahum et al reported a case series of 21 pediatric patients with retinoblastoma, 13 of whom had bilateral retinoblastoma and received external beam radiation therapy to a median dose of 32.3 Gy.…”
Section: Discussionmentioning
confidence: 99%
“…In a larger case series of 36 pediatric patients with bilateral retinoblastoma, Anteby et al reported a 3% rate of severe socket contracture at a median follow-up time of 36 months. 14 The significantly lower rates of severe socket contracture in patients with retinoblastoma than in patients with uveal melanoma could be explained by the lower dose of radiation used. It could also be explained by the fact that most retinoblastoma patients who undergo radiation therapy may not have had significant surgery; surgical intervention may have an additive effect to contracture of the socket.…”
Section: Discussionmentioning
confidence: 99%
“…Most previous investigations of cataracts after EBRT for Rb had relatively small sample sizes, short follow-up periods of less than 15 years, and no information on other potential risk factors resulting in large variability in risk estimates (6, 7, 1014). This report presents long-term follow-up of one of the largest cohorts of adult Rb survivors to investigate the risk for cataract extraction associated with therapeutic exposure of ionizing radiation to the lens of the eye.…”
Section: Introductionmentioning
confidence: 99%